2020
DOI: 10.1016/j.cell.2020.04.047
|View full text |Cite
|
Sign up to set email alerts
|

Metabolic Regulation of the Epigenome Drives Lethal Infantile Ependymoma

Abstract: Highlights d Hypoxic microenvironment is essential for propagation and growth of PFA ependymoma d Hypoxia controls metabolic intermediates that maintain an H3K27 hypomethylated genome d Inhibition or potentiation of histone lysine methylation diminishes PFA survival d Gliogenic lineage of developing fetal hindbrain mirrors PFA metabolic alterations

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
84
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
2
1

Relationship

2
6

Authors

Journals

citations
Cited by 86 publications
(96 citation statements)
references
References 78 publications
7
84
0
Order By: Relevance
“…Although adult-onset cancers are often linked to lifestyle and environmental risk factors while heritable and in utero exposures predominate in pediatric cancers, very few non-genetic risk factors have been identified for CNS malignancies [ 39 ]. While pediatric ependymomas have distinct genomic profiles from their adult counterparts, most notably in the epigenetically-driven EPN-PF-A subgroup that was not associated with telomere length in our analyses, telomerase reactivation has been observed to varying degrees across ependymoma subgroups and ages of onset [ 23 , 30 , 35 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although adult-onset cancers are often linked to lifestyle and environmental risk factors while heritable and in utero exposures predominate in pediatric cancers, very few non-genetic risk factors have been identified for CNS malignancies [ 39 ]. While pediatric ependymomas have distinct genomic profiles from their adult counterparts, most notably in the epigenetically-driven EPN-PF-A subgroup that was not associated with telomere length in our analyses, telomerase reactivation has been observed to varying degrees across ependymoma subgroups and ages of onset [ 23 , 30 , 35 ].…”
Section: Discussionmentioning
confidence: 99%
“…Our observation that genetic predisposition to longer LTL is associated with adolescent-onset and adult-onset ependymoma, but not childhood-onset ependymoma, supports this multi-step model of tumorigenesis in patients ages 12 and up. Longer telomere length may be an important mediator of ependymoma risk in adolescents and adults, where the tumor is more dependent upon acquiring somatic driver mutations and does not arise from an epigenetically dysregulated developmental cell lineage [ 26 , 35 ].…”
Section: Discussionmentioning
confidence: 99%
“…During the final stages of this work, two papers with related and partially overlapping results have appeared (Gojo et al, 2020;Michealraj et al, 2020). Based on a series of experiments involving in vitro culture of patient-derived tumor cells under hypoxic conditions, Michealraj et al (Michealraj et al, 2020) found that hypoxic programs are important drivers of pediatric PFA ependymoma tumorigenesis, and related these programs to the hypoxic environment of the early embryo. On the other hand, Gojo et al (Gojo et al, 2020) performed single-cell RNA-seq of a large cohort of pediatric ependymal tumors across multiple molecular groups and found the same tumor-derived cell differentiation trajectories for PFA ependymal tumors.…”
Section: Discussionmentioning
confidence: 99%
“…Table 5). Recent genome-wide CRISPR-Cas9 inhibition screens have revealed that ITGA6 is highly and specifically essential in PFA ependymoma cell lines compared to glioblastoma (GBM) cell lines and fetal neural stem cells (fNSCs) 26,27 (Suppl. Figure 3c).…”
Section: Pfa Ependymomas Are Dependent On Integrin α6mentioning
confidence: 99%
“…Table 7). To investigate whether such potential DNA methylation-mediated insulator dysfunctions can be linked to the transcriptional activation of genes essential for PFA ependymoma, we compared our results with those of a genetic inhibition screen in PFA cell lines 26 4d) 26,27 . By genetic (CRISPR-Cas9) inhibition experiments we validated that ARL4C is highly and specifically essential for the growth of PFA ependymoma (Figure 4h) compared to RELA ependymoma and glioblastoma models (Suppl.…”
Section: Hypermethylation Disrupts Ctcf Binding In Pfa Ependymomamentioning
confidence: 99%